Determination on the level of adoption of IPM Technology in western Nepal - Khanal, Arjun; Regmi, Punya Prasad; KC, Gopal Bahadur; KC, Dilli Bahadur; Dahal, Kishor Chandra (International Journal of Environment, Agriculture and Biotechnology, 2020)
Integrated Pest Management (IPM) is as a broad based approach for economic control of pests. A study on determination of level of adoption of IPM technology was conducted in the Banke and Surkhet districts of Nepal. For determining the spread of information and level of adoption, farmers were asked a series of questions during the survey to determine knowledge of IPM and level of IPM adoption. Using descriptive statistics and differences in means, analysis was done on relationships among access to information, IPM knowledge and adoption. This study revealed that 51.13% of the population were male with an average family size was 6.45. Almost half of the respondents had adopted IPM practices for vegetable production by receiving advice or getting training about IPM technology through agriculture officer, Market Planning Committee, I/NGOs, etc. Market Planning Committee has played a vital role in spreading IPM knowledge and information quickly, followed by mass media, as MPCs allow farmers to aggregate smallholder produce to meet market demand. Several farmer organizations join together and elect representatives to serve on the board of the MPC and have regular monthly meeting so that they could discuss on IPM technology and marketing strategy of the products. MPC group has been identified more effective in improving knowledge of IPM than other farmers’ groups.